Ethical and scientific considerations of the beginning of life on eugenic abortion in disabling genetic diseases in Peru - Abarca Barriga, Hugo Hernán (Acta Bioethica, 2023)
The article presents current biological concepts, as well as some philosophical approaches to the beginning of life, which will be examined in relation to the need for eugenic abortion. The concept of “exdurantism” is presented, in which the combination of the new nuclear and mitochondrial genome makes the individual unique; furthermore, the genomic complex is conceived as a "somatic integrator" that directs embryonic development, and the problematic is shown in the case of rape that causes pregnancies, eugenic abortion in incapacitating genetic diseases or the use of embryos after in-vitro fertilization. The dignity of the person begins at conception. When a serious or lethal genetic disease is detected, economic and social support, diagnosis and treatment should be offered; in addition, public health should invest more in screening, diagnosis, management and research strategies.